Pemanfaatan Bubuk Kulit Kacang Tanah Sebagai Substitusi Dalam Pembuatan Éclair - Ira Handayani; Widya Safira Nur Afifah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
Éclair is a type of processed pastry made from flour, water, butter, and eggs that has a cavity in the center which is generally filled with vla filling. The purpose of this research is 1) To determine the public acceptance of peanut shell powder substitution products for making éclairs. 2) To determine the best formula for utilizing peanut shell powder as a substitute in making éclairs. The research methods used are literature, documentation, experiments, and sensory evaluation. experiments in this study were performed 4 times. The results showed that the most preferred éclair product was the product with formula B, that is, éclair with an 8% substitution of groundnut shell powder. Based on sensory evaluation, the best éclair recipe was found to be 138g wheat flour, 6g groundnut shell powder, 100g margarine, 2g salt, 250 ml water, and 2 eggs. Suggestions given include: 1) More research needs to be done to test the nutritional content of the éclair. 2) Further research is needed so that groundnut shell powder can be used as an additional ingredient for various other dishes. 3) Give special treatment to groundnut shell powder when buying, by sifting again, so that it does not leave a jagged texture..